Dendrobium officinale Regulates Fatty Acid Metabolism to Ameliorate Liver Lipid Accumulation in NAFLD Mice. (19th March 2021) - Lei, Shan-Shan; Zhang, Ning-Yu; Zhou, Fu-Chen; He, Xinglishang; Wang, Hui-Ying; Li, Lin-Zi; Zheng, Xiang; Dong, Ying-Jie; Luo, Rong; Li, Bo; Jin, Hai-Ying; Yu, Qiao-Xian; et al.
Abstract : Dendrobium officinale (DOF) is a traditional Chinese edible and officinal plant. Ultrafine DOF powder (DOFP) can regulate lipids and histopathology in the liver, but the underlying mechanisms of hepatic fatty acid (FA) metabolism, which is generally correlated with the development of nonalcoholic fatty liver disease (NAFLD), remain unclear. The purpose of the present study was to investigate whether DOFP treatment alters hepatic FA metabolism in NAFLD mice by using multidimensional mass spectrometry-based shotgun lipidomics (MDMS-SL) and analyse the underlying mechanisms. A 3-week DOFP treatment prevented lipid deposition and improved hepatic histopathology in NAFLD mice after withdrawal from the high-sucrose, high-fat (HSHF) diet, and it decreased triglyceride and FA content in the liver. Furthermore, the C16 : 0/C14 : 0 and C18 : 1/18 : 0 ratios in FAs were significantly decreased in the DOFP treatment group, and the C20 : 4/C20 : 3 and C22 : 4/C22 : 3 ratios were increased, and saturated FA was inhibited. Additionally, DOFP treatment significantly increased the content of two FA β -oxidation-related proteins (carnitine palmitoyltransferase 1- α and acyl-coenzyme A oxidase 1). It also decreased the content of a FA synthesis-related protein (fatty acid synthase), a FA desaturation-related protein (stearoyl-coenzyme A desaturase-1), and a FA uptake-related protein (fatty acid transport protein 2). Moreover, DOFP treatment improved dysregulated levels of major phospholipids in the livers of model mice. The results of this study confirm that DOFP treatment in NAFLD mice has liver recovery effects by regulating FA metabolism.